Climate change and urban stormwater: vulnerability analysis of the 2010 floods in Lomé, Togo - Attipo, Reisch Vanel; Emvoulou, Innocent Joachim; Coffi, Aholou Cyprien (Frontiers in Climate, 2023)
This manuscript assesses the vulnerability to flooding between June and August 2010 in Lomé, Togo. To this end, we administered a survey to 312 inhabitants of different areas affected by flooding. The flood risk assessment methodology is based on the analysis of socio-economic indicators, risk exposure indicators, sensitivity indicators and indicators relating to the recovery capacity of flood victims. The analyses showed that 61.5% of respondents had no perception of the risk, compared with 38% who were aware of a very low level of risk compared with 2010. In addition, 84.2% of people living in areas vulnerable to flooding said they were not aware of the risk of flooding in their area. The government's assistance consisted of emergency supplies (food, medicines and temporary accommodation) for the most vulnerable sections of the population. The relevance of this research is not limited to understanding vulnerability to flooding, as it also brings new clarity to the relationship between urban management and socioeconomic challenges. This research shows that vulnerability has been exacerbated by socioeconomic insecurity and the inadequacy of sanitation facilities.